PENGARUH KOMPETENSI APARATUR SIPIL NEGARA DAN KUALITAS SISTEM AKUNTANSI INSTANSI TERHADAP KUALITAS PENYAJIAN DANA DEKONSENTRASI DALAM LAPORAN KEUANGAN DI PROVINSI SULAWESI UTARA - Pontoh, Arthur Johanes; Nangoi, Grace B.; Lambey, Robert (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
The purpose of this study aims to know the influence of State Civil Apparatus competence and system quality of agency accounting on the quality of presentation of deconcentration funds in the financial statements in North Sulawesi. Data collection by questionnaire from 42 respondents in Regional Apparatus Work Unit in North Sulawesi which manages deconcentration funds. Data were analyzed using Multiple Linear Regression analysis method with the help of SPSS 22. The results of this study indicate that the State Civil Apparatus competence partially has an effect on the quality of presentation of deconcentration funds in the financial statements with test results (thitung 2,573 > ttable 2,02269 and the significance value is 0,014 < 0,05). While system quality of agency accounting does not affect the quality of presentation of deconcentration funds in the financial statements with test results (thitung 0,861 < ttable 2,02269 and the significance value is 0,395 > 0,05)Keywords: State Civil Apparatus Competence, System Quality of Agency Accounting, Quality of Presentation of Deconcentration Funds in the Financial Statements.